Antibacterial and antifungal activities of various solvent extracts from the leaves and stem bark of Anisophyllea laurina R. Br ex Sabine used as traditional medicine in Guinea. (20th June 2015) - Onivogui, Gbago; Diaby, Mohamed; Chen, Xiaotian; Zhang, Huaiyuan; Kargbo, M'balu Regina; Song, Yuanda
Abstract: Ethnopharmacological relevance: Anisophyllea laurina R. Br ex Sabine is a plant that has been used in the folk medicine to treat malaria, dysentery, diabetes and toothache against bacterial infection. Through this study, most likely we are reporting for the first time, its effectiveness as an antibacterial and antifungal agent. Aim of the study: To evaluate antibacterial and antifungal activities of various solvent extracts from the leaves and stem bark of A. laurina R. Br ex Sabine. Materials and methods: The various solvent extracts of leaves and stem bark were tested for antibacterial and antifungal activities against eight bacteria strains and three fungal strains using the well diffusion and micro-dilution methods. Results: Antibacterial and antifungal activities of methanol and ethanol extracts were higher than the ethyl acetate and water extract. Leaves extracts had the highest potential activity against bacteria than stem bark extracts, but showed low antifungal activity compared to stem bark extracts. They also exhibited potent growth inhibitory activity against Pseudomonas aeruginosa, Salmonella typhimurium, Escherichia coli ATCC 8739 and Bacillus subtilis with MIC value of 125 µg/mL. Conclusions: The current study confirmed that the leaves and stem bark extracts of A. laurina R. Br ex Sabine proved to be most effective as antibacterial and antifungal activities. Graphical abstract: